Progressive subchondral bone cyst formation following autologous chondrocyte implantation with all-suture anchors: a Case Report with histological evaluation - Takuma Kaibara; Eiji Kondo; Masatake Matsuoka; Koji Iwasaki; Tomohiro Onodera; Daisuke Momma; Zen-Ichi Tanei; Shinya Tanaka; Norimasa Iwasaki (BMC Musculoskeletal Disorders)
Abstract Background Subchondral bone cysts (SBCs) can significantly impact the outcomes of cartilage repair procedures such as autologous chondrocyte implantation (ACI). However, the etiology and progression of SBCs following ACI remain poorly understood. This case report highlights a progressively enlarging SBC following ACI using all-suture anchors, treated with autologous osteochondral transplantation (AOT). Case presentation A 58-year-old female with progressive right knee pain, varus alignment, and Kellgren-Lawrence grade 3 osteoarthritis underwent atelocollagen-associated ACI combined with medial opening wedge high tibial osteotomy. Longitudinal radiological assessment revealed bone hole enlargement corresponding to all-suture anchor sites, with one hole continuing to expand up to 15 months postoperatively, reaching a size of 11 × 13 × 13 mm. This expanding SBC exhibited a connection to the joint cavity via a tiny fissure, scant osteosclerotic rim on CT, and fluid intensity on MRI. Histological analysis of tissue obtained during subsequent AOT revealed several findings. The SBC was located at the anterior portion of the medial femoral condyle, just beneath the all-suture anchor. Osteochondral necrosis was observed surrounding the anchor site, with no evidence of foreign body reaction. The cyst was filled with a mucoid substance and featured an aggregation of foamy macrophages. A sclerotic wall indicative of a strain response was observed. Notably, the presence of osteoclasts along the adjacent bone surface indicated ongoing bone resorption. The patient underwent AOT, which resulted in confirmed bone union. Postoperative follow-up demonstrated successful integration of the osteochondral graft and improved knee function scores over three years. Conclusion This case report documents SBC formation following knee surgery with all-suture anchors and provides histological evaluation of such a cyst. The observed histological findings may contribute to our understanding of SBC pathophysiology in the context of cartilage repair procedures. This case underscores the importance of secure suturing techniques in high-stress areas and suggests the potential benefit of extended post-operative monitoring of SBC progression beyond one year. These observations may inform future strategies for the early detection of SBC formation and its progression, as well as timely intervention to prevent further joint damage in similar cases, though further research is needed to establish broader clinical implications.